Exploring the influence of free radicals on photolytic removal of nadolol from water: Mechanism of degradation and toxicity of intermediates - Bilić, Andrijana; Savanović, Maria M.; Armaković, Stevan; Četojević-Simin, Dragana D.; Srđenović Čonić, Branislava; Kladar, Nebojša; Armaković, Sanja J. (Frontiers in Environmental Science, 2023)
In this work, for the first time, the direct and indirect photolysis of nadolol (NAD) was investigated under different light sources (simulated solar (SS), UV-LED, and UV radiations) in ultrapure water. Indirect photolysis by H2O2 showed 1.5, 2.1, and 5.6 times higher NAD degradation efficiency than direct photolysis under mentioned irradiations. This effect was particularly pronounced in the presence of UV radiation, in which the degradation efficiency of NAD was the highest (80.2%). Computational analysis based on density functional theory calculations, together with the results of NAD photodegradation efficiency in the presence of radical scavengers (isopropanol and benzoquinone), was used to propose the NAD degradation mechanism. Sixteen degradation intermediates were proposed, along with their NMR chemical shifts. Also, this study analyzed the degree of catalase activity, lipid peroxidation, and hydroxyl radicals neutralization of NAD and its photodegradation mixtures obtained after indirect photolysis. The degree of mineralization and in vitro toxicity of NAD and its degradation intermediates obtained in the presence of UV/H2O2 were assessed.